2015
DOI: 10.1371/journal.pone.0120421
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Divergent Hexaploid Triticales Derived from Common Wheat × Rye by Complete Elimination of D-Genome Chromosomes

Abstract: BackgroundHexaploid triticale could be either synthesized by crossing tetraploid wheat with rye, or developed by crossing hexaploid wheat with a hexaploid triticale or an octoploid triticale.Methodology/Principal FindingsHere two hexaploid triticales with great morphologic divergence derived from common wheat cultivar M8003 (Triticum aestivum L.) × Austrian rye (Secale cereale L.) were reported, exhibiting high resistance for powdery mildew and stripe rust and potential for wheat improvement. Sequential fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(54 reference statements)
2
23
0
Order By: Relevance
“…They found that hexaploid lines could be spontaneously derived from primary octoploid triticales, with the retention of complete sets of A-and Bgenome chromosomes and most R-genome chromosomes, and the elimination of most D-genome chromosomes. Preferential elimination of the D genome has also been reported in other hybrids, such as the hybrids between wheat cultivar M8003 and Austrian rye [Li et al, 2015], the selfed generations of synthetic hexaploid wheat (SHW) and rye [Hao et al, 2013], the amphiploid between hexaploid wheat and A. kotschyi (genome AABBDDU k U k S k S k ) [Tiwari et al, 2010], and trigeneric hybrids between octoploid triticale and tritileymus [Li et al, 2006]. It will consequently be interesting to further elucidate this phenomenon.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…They found that hexaploid lines could be spontaneously derived from primary octoploid triticales, with the retention of complete sets of A-and Bgenome chromosomes and most R-genome chromosomes, and the elimination of most D-genome chromosomes. Preferential elimination of the D genome has also been reported in other hybrids, such as the hybrids between wheat cultivar M8003 and Austrian rye [Li et al, 2015], the selfed generations of synthetic hexaploid wheat (SHW) and rye [Hao et al, 2013], the amphiploid between hexaploid wheat and A. kotschyi (genome AABBDDU k U k S k S k ) [Tiwari et al, 2010], and trigeneric hybrids between octoploid triticale and tritileymus [Li et al, 2006]. It will consequently be interesting to further elucidate this phenomenon.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, Hao et al [2013] reported that complete hexaploid triticales with 28 intact A/B and 14 intact R chromosomes could be effectively produced via hybridization of synthetic hexaploid wheat with rye. Li et al [2015] produced 2 hexaploid triticales exhibiting high resistance to powdery mildew and stripe rust, which derived from common wheat cultivar M8003 × Austrian rye. In the present study, 23 plants (57.5%) with 2n = 42 had 11-14 rye chromosomes, and the average chromosome configuration was 1.21 I + 16.22 II (ring) + 4.16 II (rod) + 0.01 III per cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although genes involving resistance to stripe rust and powdery mildew located on the widely used 1RS derived from Petkus rye are no longer completely effective to the new epidemic races, continuous efforts have been underway to search for new sources of 1RS that contain agronomically useful genes. Several new 1BL.1RS translocation lines derived from different rye varieties were developed (Ko et al., ; Li, Guo, et al., ; Li, Zhu, et al., ; Tsuchida et al., ), and some were secalin‐absent (Gustafson et al., ; Masoudi‐Nejad, Nasuda, McIntosh, & Endo, ). As several kinds of triticale and rye were involved in the breeding progress, the composition of rye chromosomes of ‘Certa’ used in the present study could be complicated (http://www.wheatpedigree.net/).…”
Section: Discussionmentioning
confidence: 99%
“…introgression lines of wheat 9 S. africanum Stapf (Lei, Li, Liu, & Yang, 2012 (Ko et al, 2002;Li, Guo, et al, 2015;Li, Zhu, et al, 2015;Tsuchida et al, 2008), and some were secalin-absent (Gustafson et al, 2008;Masoudi-Nejad, Nasuda, McIntosh, & Endo, 2002). As several kinds of triticale and rye were involved in the breeding progress, the composition of rye chromosomes of 'Certa' used in the present study could be complicated chromatin was greatly decreased (Graybosch, Peterson, & Chung, 1999;Zhou et al, 2004).…”
Section: Occurrence Frequency Of Rye Chromosomes In Progenymentioning
confidence: 99%
“…Similarly, hexaploid derivatives selected from the progeny of a set of octoploid (ABDR) triticales tend to carry the full A and B genome complement, along with chromosome 2D and chromosomes 1R and 3R-7R (Dou et al 2006). Structural alterations to chromosomes are not an uncommon occurrence when plants are in the aneuploid state (Lapitan et al 1984;Alkhimova et al 1999;Fu et al 2013;Li et al 2015). The present analysis revealed an unusual FISH profile for both chromosomes 1A and 4A in Xiaoyanmai 7, consistent with their having suffered a reciprocal translocation involving the two long arms.…”
Section: Discussionmentioning
confidence: 99%